La canso est-elle de la poésie didactique ? Enquête dans la poésie des troubadours au douzième et treizième siècles - Pierre Levron (Carnets)
The canso of the troubadours is devoted to the expression of love. It is a didactical poetry? Does it learn to love, or to be careful to the traps of love? The dangerous experience of the melancholia is one of its most important subjects. This article will to examine tree points. The first one is the lyric definition of the melancholia, which is built in a parallel to the medical models; the nature of the lover or of the beloved one, which can make the melancholy possible or impossible; the conflict between the ideal and the reality, and, for the last point, the solutions for the love melancholy, and the questions they cause.